Gut check : unleash the power of your microbiome to reverse disease and transform your mental, physical, and emotional health - Gundry, Steven R.; Lipper, Jodi (Harper Wave, an imprint of HarperCollins Publishers, 2024)
"In this addition to his New York Times bestselling Plant Paradox series, Steven R. Gundry, MD offers a guide to the gut biome and its control over its home-us!-revealing the unimaginably complex and intelligent ecosystem controlling our health and teaching us how to heal our guts to prevent and reverse every type of disease"--